Innovation culture in small and medium-sized enterprises the importance of soft factors in early stages of the innovation process - Kociánová, Petra (2010)
The study at hand investigates innovation systems at small and medium enterprises (SMEs) focusing on innovation culture, organization and company goals at the early stages of innovation process. Past research studies suggest the early stages of innovation process are critical for the overall innovation ability, however, there is a lack of literature on the specifics of innovation systems at SMEs. Case studies of 3 companies provide an overview of characteristics of innovation systems at a typical SME as well as a solid basis for drawing business implications relevant for establishing or improving its innovation system. Furthermore, the findings reveal that people management at the early stages of innovation process is missing, and that a foreign subsidiary of an international SME is relevant for an effective corporate innovation process. Implications for further research on the topic are also discussed.